Aplikasi Digital Kearifan Lokal Tarian dan Busana Tari Bali Berbasis Android - Putu Wirayudi Aditama; I Dewa Gede Agung Pandawana; Rizkita Ayu Mutiarani; Dewa Ayu Novi Swijayanti; I Gede Iwan Sudipa (JUSIFO : Jurnal Sistem Informasi, 2022)
Bali has various types of traditional dances with their distinctive functions and clothing depending on the dance's function, story, and movement. UNESCO recorded 9 Balinese dances from every district in Bali. But along with the times, one of the local wisdom in the form of Balinese dance is starting to become unattractive to the younger generation. The purpose of the research is to create a Balinese dance mobile application, so that it can preserve local wisdom of dance and dance clothing and the application can be a medium of information for the younger generation while keeping abreast of technological developments. This study uses primary and secondary data collection methods: interviews, observation, documentation, and literature study. The results of the study are in the form of an android-based application that can be downloaded for users and can be used by the younger generation to recognize and know the history of Balinese dance, classification of Balinese dance, types of dances, functions, clothing used, accompaniment instruments, and staging time for every detail of 9 types of Balinese dances and the fashion used. This application has gone through the process of testing the system's functional requirements validation with valid status.